Chapter 14. Potato Production: VPH ch. 14, CV131/HS733, rev. 6/2024 - Zotarelli, Lincoln; Dittmar, Peter J.; Roberts , Pamela D.; Desaeger, Johan; Fletcher, Prissy; Wells, Bonnie (EDIS, 2024)
Chapter 14 of the Vegetable Production Handbook of Florida